(untitled) (Nexo Revista Científica, 2020)
The purpose of this study is to investigate the effective indexes of damage to a building, with the aim of reducing the possible events caused by the earthquake and presenting a model based on spatial information systems. So, after collecting the data and information required by field method and statistical blocks, a spatial database was obtained. Then, the effectiveness of each of the criteria was based on the creation of a binary comparison matrix and questioning experts from the subject The study was obtained. In the end, in order to establish a link between the influential factors and the estimation of the final vulnerability of each building, a formula was presented in which all the effective factors were involved with the emphasis on the level of effectiveness of each building. Using expert selection software, the indexes were evaluated in terms of weight and value. Finally, the geospatial information system of GIS evaluated the magnitude and severity of the earthquake in different ranges and its consequences in terms of the indices studied for the buildings in the study area.